An incarcerated internal hernia of the sigmoid colon through a defect in the broad ligament: A case report - Ohno, Shinya (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: Hernias through a defect of the broad ligament are rare, accounting for only 1.6–5% of internal herniations [1]. This report describes a rare case of sigmoid colon obstruction due to hernia through a defect of the broad ligament, which was diagnosed before surgery. CASE PRESENTATION: A 78-year-old multiparous woman presented with lower abdominal pain and nausea. Contrast-enhanced multi-detector CT (MDCT) demonstrated a dilated sigmoid colon and edematous mesentery of the sigmoid colon in the left Douglas' fossa, the uterus was compressed dorsally to the right and the left ovary was compressed ventrally. We diagnosed an internal broad ligament defect hernia with incarceration of the sigmoid colon, and performed emergency laparotomy. The necrotic sigmoid colon was resected and anastomosis was performed by the double stapling technique. The postoperative course was uneventful. CLINICAL DISCUSSION: We consider the treatment of hernia of sigmoid colon through a broad ligament defect. CONCLUSION: We recognize that there is a possibility that, in addition to the small intestine, proximally located organs may be incarcerated. In the case of the colon, we should choose the treatment method carefully according to whether or not the colon is expected to be necrotic.